Increased mitochondrial protein import and cardiolipin remodelling upon early mtUPR - Poveda Huertes, Daniel; Taskin, Asli Aras; Dhaouadi, Ines; Myketin, Lisa; Marada, Adinarayana; Habernig, Lukas; Büttner, Sabrina; Vögtle, Friederike-Nora (PLoS Genetics, 2021)
Mitochondrial defects can cause a variety of human diseases and protective mechanisms exist to maintain mitochondrial functionality. Imbalances in mitochondrial proteostasis trigger a transcriptional program, termed mitochondrial unfolded protein response (mtUPR). However, the temporal sequence of events in mtUPR is unclear and the consequences on mitochondrial protein import are controversial. Here, we have quantitatively analyzed all main import pathways into mitochondria after different time spans of mtUPR induction. Kinetic analyses reveal that protein import into all mitochondrial subcompartments strongly increases early upon mtUPR and that this is accompanied by rapid remodelling of the mitochondrial signature lipid cardiolipin. Genetic inactivation of cardiolipin synthesis precluded stimulation of protein import and compromised cellular fitness. At late stages of mtUPR upon sustained stress, mitochondrial protein import efficiency declined. Our work clarifies the enigma of protein import upon mtUPR and identifies sequential mtUPR stages, in which an early increase in protein biogenesis to restore mitochondrial proteostasis is followed by late stages characterized by a decrease in import capacity upon prolonged stress induction.
Gesehen am 20.08.2021